Altruistic production and distribution planning in the multilayer dual-channel supply chain: Using an improved NSGA-II with lion pride algorithm. (February 2023) - Lin, Chun-Cheng; Liu, Wan-Yu; Peng, Yi-Chun; Lee, Tien-Kang
Highlights: Modelling altruistic bi-objective production and distribution with dual channels. Maximizing the profits form online and retail sales and the order fulfillment rate. Flexible altruistic pricing resolves channel conflicts while preventing losses. Solved by improved NSGA-II-LPA with slope index and multiple crossover and mutation. By simulation, altruism increases the retailer profit, reducing channel conflicts. Abstract: To achieve long-term stable development of the supply chain with online and retail channels, manufacturers may employ altruistic pricing strategies to increase retailers' interests while considering their own interests. Therefore, this work creates a mixed-integer linear programming (MILP) model for planning altruistic production and distribution for a manufacturer in a multilayer dual-channel supply chain, while maximizing the total profit of both the manufacturer and retailers and the order fulfillment rate from the manufacturer to retailers. Different from previous works using fixed altruistic pricing, this model allows flexible altruistic pricing. Since MILP is NP-hard, this work further solves this problem by an improved nondominated sorting genetic algorithm II (NSGA-II) with lion pride algorithm (LPA), in which the NSGA-II is commonly used for solving bi-objective optimization problems; the LPA adopts the slope index measure to resolve the difficulty in distinguishing the solutions with similar performance at the later stage of the NSGA-II; and multiple crossover and mutation operators are integrated to increase diversity of solutions. Simulation results show that as compared with the selfish pricing strategy, the proposed altruistic pricing strategy significantly increases the proportion of the profit of retailers, so that the channel conflict between the manufacturer and retailers can be alleviated.